Thematic evidencing of youth-empowering interventions in livestock production systems in Sub-Sahara Africa: a systematic review - Nchanji, Eileen Bogweh; Kamunye, Kelvin; Ageyo, Collins (Frontiers in Sustainable Food Systems, 2023)
Five to seven in every 10 people in Sub-Saharan Africa (SSA) are youths. They have significantly low employment rates but are unattracted to agriculture. Recently, the sector has witnessed considerable efforts by African governments to promote youth participation. While these efforts have started to bear fruits, salient gender issues remain hard to address and solve promptly. For example, youth empowerment issues—whether mutual or emancipative, asset ownership, taboos and cultural expectations, perceptions against climate change, and use of technology and ICT significantly influence livestock production among pastoralists and agro-pastoralists. While these problems are partly known and being solved, it is to be understood the extent and the salient gender issues that drive youth participation in livestock production. To understand this, we conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to thematically synthesize and evidence the youth-empowering interventions in livestock production systems in Sub-Sahara Africa. Peer-reviewed studies were retrieved from online databases (Scopus, Google ScholarTM, and gray literature). The findings show that youth face significant barriers to participating in livestock systems ranging from limited empowerment, limited access to productive assets and land, social-cultural limitations and inadequate youth-focused policy implementation. Despite the hurdles, youths, and other actors are employing various mechanisms to overcome them and enhance their participation in livestock systems. They utilize self-driven approaches such as gifting animals amongst themselves, forming saving groups commonly referred to as merry-go-rounds and belonging to community group formations as a form of social capital to empower themselves mutually. Education is also an empowerment tool for youths in the livestock sector. Emancipative empowerment through participation in political and community-level leadership is taking shape, though still in its infancy. There are opportunities presented by small ruminants and poultry where women and youths are getting a voice in the community by becoming relatively income independent and desisting from waiting for the inheritance of large livestock and assets from men. Opportunities presented by ICT in the field of livestock have been taken advantage of through the use of various apps and internet tools to enhance youth participation in livestock systems.